The concise encyclopedia of Islam - "Glasse Cyril" (Stacey International Singapore, 2001)
The Concise Encyclopedia of Islam by Cyril Glasse is a reference book that provides a comprehensive overview of Islamic terms, concepts, figures, and history. This encyclopedia covers a wide array of topics relevant to Islam, including theology, law, culture, and practices. Written in accessible language, it aims to inform readers about the complexities and nuances of Islamic thought and its impact on society and culture worldwide. Each entry is designed to give a concise yet thorough explanation, making it a valuable resource for students, scholars, and anyone interested in gaining a deeper understanding of Islam.